Politik Hukum Kriminalisasi Pelaku Perkawinan Sejenis dalam Perspektif Hukum Pidana di Indonesia - I Nengah Nuarta; Mochamad Sukedi (Jurnal Preferensi Hukum, 2024)
Same-sex relationships are often a topic of conversation for the entire community, especially religious leaders, because this violates the norms or religious values that apply to each religion. Such conditions clearly cause concern for everyone, so there is a need for strict regulations for perpetrators of same-sex marriages, either by criminalization efforts in the form of strict criminal sanctions. Based on the background above, the researcher is very interested in studying: 1. How is the regulation of marriage based on positive law in Indonesia today? and 2. How are the regulations for criminal sanctions against perpetrators of same-sex marriages in the future? This research is a normative legal research. The regulation of marriage based on positive law in Indonesia is currently regulated in the Marriage Law. Regulation of criminal sanctions against perpetrators of same-sex marriages in the future is very necessary because in order to provide legal legitimacy to the process of handling same-sex marriages so as not to give rise to conflicts that lead to violence in society is by using criminal law